Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/fuce.200500260
|View full text |Cite
|
Sign up to set email alerts
|

Material Aspects of the Design and Operation of Direct Borohydride Fuel Cells

Abstract: The direct borohydride fuel cell (DBFC) has attracted increasing interest as a potential high power source for mobile and portable applications. Engineering design plays an important role in the development of the DBFC. This paper reports data for the selection of anode, cathode, and membrane materials for the DBFC. The best DBFC performance is achieved with a Au anode, a Pt cathode, and a 3541P ion exchange membrane. The use of non‐precious catalysts, e.g., Ag, leads to promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…It has been reported that the cathode kinetics is more efficient when using oxygen instead of air [24]. Furthermore, it has been demonstrated that carbonate is formed due to the presence of CO 2 in air, which exerts a negative effect on the fuel cell performance [10,24]. Although DBFCs using air do not yield as good a performance as those using oxygen, it is desirable to develop DBFCs with air as the oxidant, simply because it is readily available in nature and may avoid the use of extra equipment and gas supply.…”
Section: Cell Performance Of Dbfcs Using Oxygen or Air As The Oxidantmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the cathode kinetics is more efficient when using oxygen instead of air [24]. Furthermore, it has been demonstrated that carbonate is formed due to the presence of CO 2 in air, which exerts a negative effect on the fuel cell performance [10,24]. Although DBFCs using air do not yield as good a performance as those using oxygen, it is desirable to develop DBFCs with air as the oxidant, simply because it is readily available in nature and may avoid the use of extra equipment and gas supply.…”
Section: Cell Performance Of Dbfcs Using Oxygen or Air As The Oxidantmentioning
confidence: 99%
“…(9)(10)(11) As a result, the theoretical potential of the overall cell reaction increases to 3.01 V:…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Chronoamperometry results demonstrated a fast signal response, and the sensitivity was determined as 1.56 ± 0.13 μA/100 μM based on the present disk electrode. The use of sodium borohydride in portable power systems has attracted increasing interest in hydrogen and fuel cell applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] since Amendola et al developed a direct borohydride fuel cell (DBFC) with high power density 17 and a portable hydrogen generator using borohydride hydrolysis.18 Theoretically, sodium borohydride has the capability of transferring 8 electrons per molecule at a low electrode potential of −1.24 V SHE theoretically providing a high specific energy of 9,296 Wh kg −1 (based on 1.64 V cell voltage corresponding to oxygen reduction at the cathode). However, the spontaneous hydrolysis of sodium borohydride, (which is the objective in a hydrogen generator) reduces the Faradic efficiency in practical DBFC applications.…”
mentioning
confidence: 99%
“…The electron transfer number indicated in the Fig. 1 Gold, which has generally been described in the literature as inactive for the hydrolysis of borohydride and the oxidation of hydrogen, [8][9][10][11][12][13][14][15][16][17] was first proposed in 1991 as an electrode for the determination of borohydride concentration. 31 There is no other reference reporting the electrochemical detection of borohydride.…”
mentioning
confidence: 99%